Mutational landscape, clonal evolution patterns, and role of RAS mutations in relapsed acute lymphoblastic leukemia - Oshima, Koichi; Khiabanian, Hossein; da Silva-Almeida, Ana C.; Tzoneva, Gannie; Abate, Francesco; Ambesi-Impiombato, Alberto; Sanchez-Martin, Marta; Carpenter, Zachary; Penson, Alex; Perez-Garcia, Arianne; Eckert, Cornelia; Nicolas, Concepción; et al. (Proceedings of the National Academy of Sciences - PNAS, 2016)
Although multiagent combination chemotherapy is curative in a significant fraction of childhood acute lymphoblastic leukemia (ALL) patients, 20% of cases relapse and most die because of chemorefractory disease. Here we used whole-exome and whole-genome sequencing to analyze the mutational landscape at relapse in pediatric ALL cases. These analyses identified numerous relapse-associated mutated genes intertwined in chemotherapy resistance-related protein complexes. In this context, RAS-MAPK pathway-activating mutations in the neuroblastoma RAS viral oncogene homolog (NRAS), kirsten rat sarcoma viral oncogene homolog (KRAS), and protein tyrosine phosphatase, nonreceptor type 11 (PTPN11) genes were present in 24 of 55 (44%) cases in our series. Interestingly, some leukemias showed retention or emergence of RAS mutant clones at relapse, whereas in others RAS mutant clones present at diagnosis were replaced by RAS wild-type populations, supporting a role for both positive and negative selection evolutionary pressures in clonal evolution of RAS-mutant leukemia. Consistently, functional dissection of mouse and human wild-type and mutant RAS isogenic leukemia cells demonstrated induction of methotrexate resistance but also improved the response to vincristine in mutant RAS-expressing lymphoblasts. These results highlight the central role of chemotherapy-driven selection as a central mechanism of leukemia clonal evolution in relapsed ALL, and demonstrate a previously unrecognized dual role of RAS mutations as drivers of both sensitivity and resistance to chemotherapy.